Interrupting the darkness: Law setting limitations on the duration of the night-shift work for BPO employees - Paca, Francis Christian Mark T. (Animo Repository, 2018)
This thesis explores the necessity of prohibiting indefinite night-shift work for Business Process Outsourcing (BPO) employees in the Philippines. The BPO industry involves the receiving of work activities outsourced by clients from other jurisdictions. Filipino workers accept these work orders and perform them depending on the timezone of the BPO client. Hence, the BPO industry operates on a 24-hour basis, and as a result, many of its employees are exposed to night-shift work. There have been studies linking night-shift work schedules with health issues such as hypertension and sleep deprivation, due to the inability of the human body to adjust to long periods of night shift work and the highly-stressful nature of the employment. The BPO industry has contributed greatly to the Philippine economy in terms of revenues and job creation. With the continued increase of the industry, more employees are expected to join its ranks, carrying along a greater number of individuals potentially exposed to the hazards of night-shift work. The BPO industry has gained importance in the Philippine economy, as it has provided employment to an estimated 1.15 million employees1, whose efforts brought in $22 Billion in revenues in 20152. Notwithstanding the inevitability of night-shift work due to time zone differences between the Philippines and the countries of the BPO clients, the healthcare facilities provided for the employees, provisions for night differential, and recognition from different branches of the Government, there is still no law that addresses the root of the problem, which is the continued exposure to nightshift work. This thesis suggests the passage of a law that would protect workers from permanent night-shift work for BPO employees. The 24-hour nature of the industry shows that the assignment of workers to night-shift schedules is inevitable, and a total prohibition on night-shift work would not be ideal. Furthermore, the lack of industry protection and collective employee action to address the problem necessitates legislative intervention. Given the employment opportunities and income the industry provides the Philippines and Filipinos, a law limiting the exposure of workers to such indefinite periods of night-shift work is timely, as the continued expected growth of the industry would only mean a further increase in the number of employees to be affected. The law would impose a requirement that employees be informed of a definite conclusion to the assignment to a night-shift schedule, and that such period not extend beyond 6-months. The law would be based on the State’s police power, the Constitutional protection of labor, the Civil Code, jurisprudence on the protection of labor, as well as previous attempts by the legislature to provide such protection. The proposed law would also be a recognition that the employer’s right to returns on its investments can coexist with such protective measures by the State.